Neurolymphomatosis: Unusual Extranodal Involvement Pattern on 18F-FDG PET/CT in a Non-Hodgkin Lymphoma Recurrence - Mosmann, Marcos Pretto; Sprinz, Clarice; Raupp, Ana Amélia; da Silva, Thiago Krieger Bento; de Abreu, Henrique Rodrigues (Clinical and Biomedical Research, 2011)
A 37-year-old woman was diagnosed with Stage IVB diffuse large-B cell lymphoma, presenting with bulky mediastinal and bone marrow involvement. She was treated with 8 cycles of R-CHOP and radiotherapy, achieving complete remission on CT. Two months latter, she presented with pain and weakness in the lower limbs. The ENM, MR and the CSF analysis had shown evidence of lymphoma recurrence with initiation of intrathecal chemotherapy. Her disease continued to progress despite treatment. The following PET/CT shows multiple hypermetabolic areas, compatible with extranodal disease and poor response to therapy, allowing change to R-ICE and autologous stem cell treatment.